The Effectiveness of E-Government Implementation in the Digital Transformation of Public Administration in 3T Regions - Suhelmi Helia; Ogie Pryanka Adhelin (CAKRAWALA : Management Science Journal, 2026)
Digital transformation is a critical strategy for enhancing efficiency and accountability in public administration. However, e-Government implementation in Indonesia's disadvantaged, frontier, and outermost (3T) regions faces significant challenges, including limited infrastructure, low digital competence, and institutional constraints. This study analyzes the effect of e-Government on public administration effectiveness, focusing on ICT infrastructure, employee digital competence, organizational change management, and internal regulatory support. Using a quantitative approach, data were collected from 100 civil servants in the Mentawai Islands Regency via structured Likert-scale questionnaires and analyzed through multiple linear regression. Results show that all variables positively and significantly affect administrative effectiveness, both partially and simultaneously. ICT infrastructure improves service accessibility, digital competence optimizes system use, change management supports transformation readiness, and regulatory support ensures governance consistency. The study concludes that successful e-Government requires an integrated approach combining technological readiness, human capability, organizational adaptability, and supportive regulation, offering practical insights for policymakers in structurally constrained regions.